A Model‐Based Systems Engineering Application for Radiometric Measurement Uncertainty. Issue 1 (13th September 2016) - Phojanamongkolkij, Nipa; Walker, Joe A.
Abstract: The current practice in radiometric measurement uncertainty of an instrument is to build the computational model in spreadsheets. Albeit easy to use, the spreadsheets are difficult for users to understand the computational structure hierarchy, and in traceability to the performance requirements. The motivation of this study is to overcome these weaknesses by transforming the spreadsheets to the Systems Modeling Language (SysML) model. The SysML model visually provides the structure hierarchy (using block definition diagrams) to the traditional spreadsheets and presents uncertainty calculations as mathematical constraints captured by parametric diagrams. In addition, the SysML requirement diagrams give requirement traceability to the uncertainty elements. The current model has been extended beyond the uncertainty analysis to include structure decomposition of the physical instrument as well as the total instrument mass analysis. A system‐level design trade analysis that encompasses both radiometric measurement uncertainty and system mass is demonstrated. The Desirability Function method is applied to optimally select the design, where both the uncertainty and mass are simultaneously considered.